Perfil de atendimentos clínicos de farmacêuticos na atenção primária de um município de Minas Gerais (Revista Brasileira Multidisciplinar, 2025)
The role of the pharmacist in health services goes beyond promoting the rational use of medicines. This study aimed to evaluate the profile of clinical care provided by pharmacists in Primary Health Care (PHC) in a municipality in Minas Gerais. This is a quantitative, analytical, cross-sectional and retrospective study developed in Primary Health Care teams based on the verification of data contained in the Electronic Health Record of the information system used by the municipality. The research results showed that the profile of people served was mostly female and aged between 20 and 59 years. There was a higher prevalence of services distributed in relation to age groups by the pharmacist integrated into the Family Health Strategy when compared to the Expanded Family Health and Primary Care Center. The majority of consultations took place in 2019 and the main International Classification of Primary Care (ICPC-2) were Arterial Hypertension (K87) and Diabetes Mellitus (T90). The presence of the pharmacist in providing assistance throughout all life cycles is extremely important. The clinical role of the pharmacist favors gaining space and recognition within PHC and, consequently, throughout the health system.Keywords: Pharmaceutical Care; Pharmaceutical Assistance; Primary Health Care.